2012
DOI: 10.1007/s00005-012-0181-2
|View full text |Cite
|
Sign up to set email alerts
|

The Classification of Microglial Activation Phenotypes on Neurodegeneration and Regeneration in Alzheimer’s Disease Brain

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease characterized by progressive decline of cognitive function and memory formation. There is no therapeutic that can halt or reverse its progression. Contemporary research suggests that age-dependent neuroinflammatory changes may play a significant role in the decreased neurogenesis and cognitive impairments in AD. The innate immune response is characterized by pro-inflammatory (M1) activation of macrophages and subsequent production of specific cytokines, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
252
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 344 publications
(263 citation statements)
references
References 223 publications
(268 reference statements)
6
252
0
5
Order By: Relevance
“…The inflammation can be acute or chronic. The inflammatory reaction that involves in most neurodegenerative diseases (Craft et al 2006;Liu et al 2013;Pizza et al 2011;Sudduth et al 2013;Varnum and Ikezu 2012), is often termed ''neuroinflammation''. Microglia, which is supposed to be the resident macrophages of the brain, and atrocities are the main cells that involve in this process.…”
Section: Inflammation In Admentioning
confidence: 99%
See 2 more Smart Citations
“…The inflammation can be acute or chronic. The inflammatory reaction that involves in most neurodegenerative diseases (Craft et al 2006;Liu et al 2013;Pizza et al 2011;Sudduth et al 2013;Varnum and Ikezu 2012), is often termed ''neuroinflammation''. Microglia, which is supposed to be the resident macrophages of the brain, and atrocities are the main cells that involve in this process.…”
Section: Inflammation In Admentioning
confidence: 99%
“…Microglia, which is supposed to be the resident macrophages of the brain, and atrocities are the main cells that involve in this process. In the brains of both AD individuals and transgenic animal models, it was found that Ab plaques are surrounded by activated glial cells (Bauer et al 1991;Cagnin et al 2001;Fillit et al 1991;Liu et al 2013;Varnum and Ikezu 2012). Activated microglia and astrocytes strongly secrete inflammatory components such as pro-inflammatory cytokines, chemokines, complement, macrophage inflammatory proteins, monocyte chemoattractant proteins, reactive oxygen species (ROS), nitric oxide (NO) prostaglandins, leukotrienes, thromboxanes and so on (Akiyama et al 2000;Griffin et al 1998;Mrak et al 1995;Town et al 2005;Tuppo and Arias 2005).…”
Section: Inflammation In Admentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are certain observations which do not concur with this hypothesis. Firstly the removal of Aβ from the brains of animal models and humans does not halt the progression of the disease and secondly Aβ is often present in healthy brains [40].…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…There is an increase in the number of 'activated' microglia cells (of unknown phenotype) surrounding senile plaques in the cerebral cortex, Aβ deposits are present in T cell, and there is a significant decrease in CD200 protein and mRNA in AD hippocampus and inferior temporal gyrus, but not cerebellum. [40]. Therefore a second hypothesis has been presented indicating that neuronal damage that occurs in AD is not entirely due to Aβ deposition or intracellular tau accumulation but caused by an abnormal immune response.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%